1996
DOI: 10.1111/j.1365-2273.1996.tb01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Hearing aids and glue ear

Abstract: This study was designed to determine the acceptance and effectiveness of a hearing aid in the management of children with persistent hearing loss due to glue ear (otitis media with effusion [OME]). Forty-eight children with OME, in whom the main symptom was deafness, were treated with a hearing aid instead of surgery and reviewed at 3-monthly intervals over 6-12 months. Seventy-one per cent reported unequivocal satisfaction with the aid. Sixty-five per cent used the aid continuously throughout the day whilst 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 7 publications
0
21
0
2
Order By: Relevance
“…In contrast to the response in our survey where the otolaryngologists opinion seems to indicate that children and parents prefer surgery to hearing aids, two publications in the UK have shown that a signi cant number of parents are willing to try hearing aids for their children. 1,2 In our survey only a small proortion of otolaryngologists mention giving the parents a balanced opinion and option for both hearing aids and ventilation tubes. It is possible that if the parents were given an informed decision-making choice then more parents would be happy to try hearing aids for their children.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the response in our survey where the otolaryngologists opinion seems to indicate that children and parents prefer surgery to hearing aids, two publications in the UK have shown that a signi cant number of parents are willing to try hearing aids for their children. 1,2 In our survey only a small proortion of otolaryngologists mention giving the parents a balanced opinion and option for both hearing aids and ventilation tubes. It is possible that if the parents were given an informed decision-making choice then more parents would be happy to try hearing aids for their children.…”
Section: Discussionmentioning
confidence: 97%
“…It is well known that hearing aids (HA) can provide excellent compensation for a purely conductive hearing loss and they can be an effective alternative to surgery with high acceptance and compliance rates [9]. And in their excellent paper, Flanagan et al in 1996 concluded that the most defined use of a hearing aid must be in managing otitis media with effusion in those children with significant recurring hearing loss despite previous surgery [9].…”
Section: Discussionmentioning
confidence: 98%
“…In a small UK study of 48 children with OME, compliance by the children issued with a hearing aid was high. However, 13% of children continued to use the hearing aid in the affected ear after the OME had resolved 8 Surgical treatment is recommended where resolution has not occurred over a 3–6 month period and there is a persistent hearing impairment with associated disability.…”
Section: Summary Of Managementmentioning
confidence: 99%
“…In a small UK study of 48 children with OME, compliance by the children issued with a hearing aid was high. However, 13% of children continued to use the hearing aid in the affected ear after the OME had resolved 8 …”
Section: Summary Of Managementmentioning
confidence: 99%